The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1046/j.1365-2621.2002.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Parboiling of rice. Part I: Effect of hot soaking time on quality of milled rice

Abstract: This study investigated the effect of soaking time on the quality of parboiled rice. The paddy was soaked in water at 25 and 80 °C for 15, 30, 45, 60 and 120 min. The soaked paddy was steamed, dried, stored and milled. With increasing soaking time a significant increase in water absorption and milling and head rice yield (hence reduction in broken rice) was observed. A significant difference in milling yield, at the 1% level, was obtained between the raw rice control and the hot soaked parboiled samples. A lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 5 publications
(12 reference statements)
4
44
0
Order By: Relevance
“…Higher soaking temperatures have known to cause expansion and softening, thus reducing the diffusion resistance. The softening of cereal grains was also reported in milled rice and white rice (Kashaninejad et al, 2007;Miah, Haque, Douglass, & Clarke, 2002;Sowbhagya, Ramesh, & AIi, 1994). Genkawa et al (2010) also showed that after 10 min of soaking, the breaking load or rigidity of rice had decreased by about 23 N upon changing the soaking temperature from 15°C to 25°C.…”
Section: Resultsmentioning
confidence: 75%
“…Higher soaking temperatures have known to cause expansion and softening, thus reducing the diffusion resistance. The softening of cereal grains was also reported in milled rice and white rice (Kashaninejad et al, 2007;Miah, Haque, Douglass, & Clarke, 2002;Sowbhagya, Ramesh, & AIi, 1994). Genkawa et al (2010) also showed that after 10 min of soaking, the breaking load or rigidity of rice had decreased by about 23 N upon changing the soaking temperature from 15°C to 25°C.…”
Section: Resultsmentioning
confidence: 75%
“…The penetration of added Fe into white-parboiled rice in this study was enhanced by soaking at elevated temperature (60°C), probably due to decreased resistance of water penetration across cell layers of the endosperm and/or enhanced ion exchange, even in a shorter time. Moreover, soaking of paddy rice at room temperature over a long period also carries the risk of deterioration of flavour from fermentation (Islam, Shimizu, & Kimura, 2002;Miah, Haque, Douglass, & Clarke, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Higher temperatures are known to expand and soften grains. Temperature induced softening has been reported for soybean (Singh & Kulshrestha, 1987), chickpea (Hung, Liu, Black, & Trewhella, 1993), kidney bean (AbuGhannam & McKenna, 1997), wheat (Maskan, 2002), rough rice (paddy) and milled rice (Miah, Haque, Douglass, & Clarke, 2002;Sowbhagya, Ramesh, & Ali, 1994). Soaking temperatures closer to the gelatinisation temperature of starch, resulted in greater water uptake.…”
Section: Effect Of Temperature On Water Uptake Kineticsmentioning
confidence: 99%